1976
DOI: 10.1111/j.1365-3083.1976.tb00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Granulocyte Neutral Proteases on Complement Components

Abstract: The proteolytic effects of collagenase and elastase from human granulocytes were investigated on the human complement components C3 and C5 in serum and with purified components. The conversion of C3 was analyzed with crossed immunoelectrophoresis as described by Ganrot, and the conversion of C5 was detected with immunoelectrophoresis according to Scheidegger's method. Collagenase converted C3 to C3b but had no detectable effect on C5. Elastase converted C3 to C3b and converted C5 to a C5b-like fragment. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
2

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(43 citation statements)
references
References 17 publications
(10 reference statements)
2
39
0
2
Order By: Relevance
“…5G). These data are consistent with early demonstrations of PMN-derived cationic and neutral protease C3 cleavage and C3a generation (60,61), as well as recent studies of ELANE C3 cleavage and C3a generation (59). Critically, in this regard, inhibition of C3a generation by EDTA in our data does not necessarily reflect C3 convertase inhibition, as EDTA has been shown to bind and inhibit ELANE (62).…”
Section: Pmn-and Mf-cm Factorssupporting
confidence: 80%
“…5G). These data are consistent with early demonstrations of PMN-derived cationic and neutral protease C3 cleavage and C3a generation (60,61), as well as recent studies of ELANE C3 cleavage and C3a generation (59). Critically, in this regard, inhibition of C3a generation by EDTA in our data does not necessarily reflect C3 convertase inhibition, as EDTA has been shown to bind and inhibit ELANE (62).…”
Section: Pmn-and Mf-cm Factorssupporting
confidence: 80%
“…Since granulocyte elastase in vitro not only inactivates C3 [6,7] but also IgG and IgM [10,11], it is conceivable that free granulocyte elastase in vivo leads to functional inactivation of these opsonins and thereby favors the persistence of microorganisms, a well known characteristic of P aeruginosa infections in these patients [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Since the activities of the three enzymes measured could possibly be attributed to the presence of PMN neutral proteases [6][7][8]29], correlations between enzymatic activities within each group were calculated. Group 1: a linear correlation was found between 125I-labeled C3-cleaving and granulocyte elastase-like activity (r = .49, P < .025) and between elastolytic and granulocyte elastaselike activity (r = .89, P < .001).…”
Section: Leukocyte Quantitation and Protein Concentra-mentioning
confidence: 99%
See 1 more Smart Citation
“…Activation proceeds through the cleavage of native C3 by either the classical (C42) or the alternative (C3b, Bb) pathway convertase of C3 or both [2,3]. Recently it has been shown in vitro [4][5][6][7][8] that C3, as well as C5, can be split by complement-unrelated enzymes, such as purified neutral proteases from PMNLs. These reports have shown that the purified granular enzymes elastase, collagenase, and cathepsin G can act on C3 and C5 by splitting small fragments similar in size to C3a and C5a from the native molecules.…”
mentioning
confidence: 99%